LA HISTORIA CONTRAATACA BY JUAN MANUEL SANTANA PÉREZ (VENEZUELA: BURIA FOUNDATION) - Gomez Gomez, Adith Shilley (2021)
The following is a review about the book titled La Historia Contraataca (History Fights Back), written by the Venezuelan historian Juan Manuel Santana Pérez. In the book, the historiographical path during the 20th century is presented by the author. Santana Pérez explains its history, its theoretical basis, and the methodology researchers employed during that period. The book is composed by nine chapters, which are reviewed in detail.